2019
DOI: 10.1002/pld3.177
|View full text |Cite
|
Sign up to set email alerts
|

MYC2 regulates ARR16, a component of cytokinin signaling pathways, in Arabidopsis seedling development

Abstract: MYC2 is a basic helix‐loop‐helix transcription factor that acts as a repressor of blue light‐mediated photomorphogenic growth; however, it promotes lateral root formation. MYC2 also regulates different phytohormone‐signaling pathways in crucial manner. Arabidopsis response regulator 16 (ARR16) is a negative regulator of cytokinin signaling pathways. Here, we show that MYC2 directly binds to the E‐box of ARR16 minimal promoter and negatively regulates its expression in a cytokinin‐dependent manner. While ARR16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 70 publications
(155 reference statements)
0
21
0
Order By: Relevance
“…We named this gene FERR (female-specifically expressed RESPONSE REGULATOR), based on evidence for its function described below. Phenotypes previously reported for mutations in two members of this A. thaliana gene family, arr16 and arr17, include effects on plant photomorphogenesis, cell division activity and root hydrotropism, but not changes in floral organs [31][32][33] . However, a recent study demonstrated involvement of such a gene in female functions and sex determination in P. tremula 29 , and named the FERR ortholog ARR17 29 (although, as discussed below, it is not the ortholog of the A. thaliana ARR17 gene).…”
Section: Resultsmentioning
confidence: 96%
“…We named this gene FERR (female-specifically expressed RESPONSE REGULATOR), based on evidence for its function described below. Phenotypes previously reported for mutations in two members of this A. thaliana gene family, arr16 and arr17, include effects on plant photomorphogenesis, cell division activity and root hydrotropism, but not changes in floral organs [31][32][33] . However, a recent study demonstrated involvement of such a gene in female functions and sex determination in P. tremula 29 , and named the FERR ortholog ARR17 29 (although, as discussed below, it is not the ortholog of the A. thaliana ARR17 gene).…”
Section: Resultsmentioning
confidence: 96%
“…The phytohormone CK inhibits root growth by promoting cell differentiation in root apical meristem (Vandenbussche et al 2007;Kieber and Schaller 2018). The atmyc2 mutants are less sensitive to the CK induced inhibition of root growth, suggesting a role of MYC2 in CK signaling pathways in regulating the root growth (Shrivastava et al 2019).…”
Section: Root Growthmentioning
confidence: 97%
“…Apart from playing a predominant role in seedling development, the ZBFs have been demonstrated to influence various other developmental processes such as seed germination, root growth, flowering time and senescence (Yadav et al 2005;Mallappa et al 2006;Gangappa et al 2010;Gangappa and Chattopadhyay 2010;Senapati et al 2019). Furthermore, ZBFs also cross-talk with ABA, JA, EL and CK signaling pathways to influence diverse signaling processes (Yadav et al 2005;Kazan and Manners 2013;Gangappa et al 2013b;Zhang et al 2014;Shrivastava et al 2019;Zhuo et al 2019 and Fig. 1).…”
Section: The Involvement Of Zbfs In Multiple Developmental Processesmentioning
confidence: 99%
See 2 more Smart Citations